Pengaruh Sarapan, Aktivitas Fisik, dan Status Gizi terhadap Pola Menstruasi Remaja di SMP 2 Meureubo - Maryam, Siti; Iskandar, Wardah; Anwar, Sufyan; Khairunnas, Khairunnas (Medan Resource Center, 2024)
This study investigates the correlation between menstrual cycle patterns, breakfast habits, physical activity, and nutritional status among adolescents at SMP 2 Meureubo. The research aims to identify key factors influencing menstrual cycle regularity. A total of 53 students were selected using a random sampling method for this cross-sectional quantitative study. Data were gathered through a structured questionnaire assessing breakfast habits, levels of physical activity, and nutritional status determined by Body Mass Index (BMI). Chi-square analysis revealed statistically significant associations, with breakfast habits (p<0.05) and physical activity (p<0.05) playing critical roles in maintaining menstrual regularity. Adolescents with consistent breakfast routines demonstrated a 77% improvement in cycle regularity, while adequate physical activity contributed to a 73% enhancement in consistency. The findings underscore the importance of balanced nutrition and physical activity in promoting healthy menstrual patterns. The study recommends targeted health education programs focusing on balanced meals, regular exercise, and consistent monitoring of nutritional health to improve adolescent menstrual health outcomes.